Rehabilitation Technical Operation Standard for Du Meridian Moxibustion of Traditional Chinese Medicine - Working Group of Rehabilitation Technical Operation Standard for Du Meridian Moxibustion of Traditional Chinese Medicine; Xiaotong WANG; Xinxin WANG; Yan LI; Yue WANG; Shengbo JIN; Jiu WANG; Dongning LIU (康复学报)
Du meridian moxibustion is a special external therapy which combines the meridian theory of traditional Chinese medicine and traditional moxibustion. This therapy are given"spreading moxibustion with ginger mud"on the spinal segment of the dorsal Du meridian with moxa and ginger, and can be combined with Du meridian moxibustion powder. It can concentrate the comprehensive effect on the lesion to maximize the effect in a short time such as meridian, acupoint, moxibustion, medicine and so on, which has the effects of reinforcing kidney and unblocking Du meridian, warming yang and dispelling cold, unblocking Du meridian and relieve pain, regulating yin and yang, etc.. It has been widely used to treat various diseases and health care. The operation standard of traditional Chinese medicine rehabilitation technology of moxibustion is mainly to standardize the management and guide the professional and technical personnel of Chinese medicine to correctly use moxibustion therapy. The standard introduces the technical scope, normative references, terms and definitions, operation steps and requirements, precautions, taboos, appendices. In particular, it focuses on the three parts of the operation steps and requirements of the standard. For example, preparation before moxibustion (preparation of wormwood and ginger mud, acupoint selection and positioning, body position selection, moxibustion supervision device and its auxiliary supplies, preparation of the subject, environmental requirements, etc.); moxibustion process (body position, acupoint selection, scraping, disinfection, moxibustion supervision powder, ginger mud paving, preparation and placement of moxibustion device, moxibustion, cleaning moxibustion place, etc.); operation steps and requirements after moxibustion. In addition, the selection of moxa and Du meridian moxibustion apparatus, the preparation of Du meridian moxibustion powder, the main role and indications of Du meridian moxibustion rehabilitation technology were also explained. It is suitable to guide the professional and technical personnel of TCM with standard rehabilitation technology operation of moxibustion. This standard is good in applicability and effectiveness.